2021
DOI: 10.3390/technologies9040100
|View full text |Cite
|
Sign up to set email alerts
|

Functional Model of a Self-Driving Car Control System

Abstract: The article describes a structural and functional model of a self-driving car control system, which generates a wide class of mathematical problems. Currently, control systems for self-driving cars are considered at several levels of abstraction and implementation: Mechanics, electronics, perception, scene recognition, control, security, integration of all subsystems into a solid system. Modern research often considers particular problems to be solved for each of the levels separately. In this paper, a paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Authors describe in this article developed models and tools for software control of vehicle systems based on the modification of the UAZ Patriot vehicle [8].…”
Section: Of 17mentioning
confidence: 99%
See 3 more Smart Citations
“…Authors describe in this article developed models and tools for software control of vehicle systems based on the modification of the UAZ Patriot vehicle [8].…”
Section: Of 17mentioning
confidence: 99%
“…Engineers must understand the criteria for deciding in that situation. End-to-end solutions also cannot be widely used because of the low performance of the computing modules used on a vehicle board [11].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The perception system-the vehicle should always know how to identify its environment, and the cognition system for decision-making, such as what the AV should do and how it should do it. Sviatov et al (2021) described a structural and functional model of an autonomous vehicle control system, intending to generate several mathematical problems. Their study identified the control system of an autonomous vehicle as a functional requirement.…”
Section: Introductionmentioning
confidence: 99%